Participation in daily life activities and its relationship to strength and functional measures in boys with Duchenne muscular dystrophy - Bendixen, Roxanna M. (2014)
PURPOSE: While most studies of Duchenne muscular dystrophy (DMD) have focused on physical impairment, there is a need to explore how impairment impacts real life experiences in order to provide intervention strategies focused on participation. Objectives were: 1) to investigate the domains of participation in a sample of boys with Duchenne muscular dystrophy; 2) to compare a younger (<10 years) and older (≥10 years) group of boys with DMD with regard to participation; 3) to investigate strength and timed functional tests in a sample of boys with Duchenne muscular dystrophy; 4) to compare a younger (<10 years) and older (≥10 years) group of boys with DMD with regard to strength and timed functional tests; and 5) to explore associations between participation and strength and timed functional tests for our DMD cohorts. METHODS: This cross-sectional study included sixty boys with DMD (mean 9.3 years ±0.3). Boys completed strength testing, timed functional tests, the Children’s Assessment of Participation and Enjoyment and the ACTIVLIM. Independent samples t-tests were used to test for differences in all measures between our younger and older cohorts; Spearman’s (rank) correlation was used to assess relationships between participation and strength and time functional tests. RESULTS: Significant differences were found between our younger and older boys with DMD in the areas of recreational (p≤0.01), social (p≤0.001), and skill-based activities (p≤0.05), as well as with whom and where the activities were performed (p≤0.05 and 0.001, respectively). Older boys with DMD report lower levels of participation in these areas, as well as less engagement in activities with individuals other than family members and less participation outside of the home. Lower levels of strength and slower rates of functional performance correlate with participation in fewer physical activities for our younger cohort and fewer physical and social activities for our older cohort. CONCLUSIONS: Strength and function relate to the variability and type of activities in which boys with DMD participate. A key finding is the significant decline in social activities and community-based engagement as the boys with DMD age. The ultimate goal of an intervention is for our children to be as actively engaged in life as they desire. This requires addressing participation when measuring outcomes in order to more fully understand limitations and provide appropriate strategies for continued participation for boys and their families.